Matematika dalam Konsep Lingkaran: Membuat Alat Pembelajaran Digital yang Menghormati Warisan Budaya - Aminah, Neneng; Firmasari, Siska; Junaedi, Lidiya; Nurfarikha, Cicih (Edumatica : Jurnal Pendidikan Matematika, 2025)
This research aims to develop mathematics learning media called ETNOSIKA-AR, which combines visual-interactive concepts with the local cultural values of the Kaliwadas Ancient Well Site in circular materials to improve students' understanding of concepts. Media development is carried out based on the ADDIE model, consists of five systematic stages: needs analysis, design, development, implementation, and evaluation. This research was conducted in June and involved high school students in class X in Cirebon. The validation results by three experts show that this media is included in the very valid category, with percentages of 94.7%, 97.9%, and 96.8%, respectively. A practicality test was conducted involving 31 high school students, and the results showed that 77% of students stated that this medium was practical, and 13% said it was very practical. On the other hand, only 10% consider it less valuable. The analysis showed that 77.42% of students were in the high N-Gain category, and 22.58% were in the medium category, with no students in the low category, with an average N-Gain score of 0.7762. These findings show that ETNOSIKA-AR media effectively improve understanding of circular matter. This media also succeeds in presenting interesting and meaningful learning by integrating cultural and technological aspects.